دور دراسة الأديان في غرس العقيدة الإسلامية للصف الخامس بكلية المعلمين الإسلامية معهد دار السلام كونتور للتربية الإسلامية الحديثة لمرحلة 2016-2017 - Rif’at Husnul Ma’afi; Muhammad Fathan Fadlilah (Universitas Darussalam Gontor, 2018)
Darussalam Gontor Modern Islamic Boarding school is one of the Islamic educational institutions that pays attention toward the study of various religion. The curriculum section of Islamic Teachers Training Collage (ITTC) has set al-Adya>n book for class 5 of ITTC, in order to strengthen the aqeeda in the hearts of the students. The students have studied different teachings on other religions at the level of fifth grade of ITTC. The researcher tries to collecting the data by interviewing the sixth grade students of ITTC and their supervisors, filing questionnaires to the sixth grade students of ITTC, and direct observation by the researcher, as well as documentation on test scores on al-Adya>n class five of ITTC. The purpose of this study is to determine the extent to which the role of al-Adya>n lesson in implant Islamic theology for class five of ITTC Darussalam Gontor Modern Islamic Boarding School on period 2016-2017. The above study shows that al-Adya>n has very big role in instilling Islamic aqeedah named the pillars of faith and practice such as praying fardhu in congregation, sunnah prayers such as rawatib prayer, hajat praying, dhuha praying, tahajud praying, and also fasting sunnah such as Monday and Thursday, and Daud fasting